2008
DOI: 10.1159/000113423
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Renal Insufficiency Patients Undergoing Coronary Artery Bypass Graft Surgery

Abstract: Renal insufficiency (RI) is a prognostic marker in patients with cardiovascular disease. In this study, the latest standard of glomerular filtration rate (GFR) calculation, that is the modification of diet in renal disease (MDRD) study equation, is used to measure the difference in the outcome of coronary artery bypass graft (CABG) surgery in various GFR groups. Between 2000 and 2005, 1,055 patients underwent CABG surgery and were categorized into 5 groups according to the National Kidney Foundation guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Chirumamilla and coworkers [8] have again demonstrated, as we have, that estimation of GFR unmasks chronic renal failure in some of the patients with normal serum creatinine levels. Their study reinforces the need for routine evaluation of renal function by GFR, calculated using the MDRD study equation, in patients undergoing CABG.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Chirumamilla and coworkers [8] have again demonstrated, as we have, that estimation of GFR unmasks chronic renal failure in some of the patients with normal serum creatinine levels. Their study reinforces the need for routine evaluation of renal function by GFR, calculated using the MDRD study equation, in patients undergoing CABG.…”
supporting
confidence: 71%
“…In this issue of Cardiology, Chirumamilla and coworkers [8] report a retrospective study comparing the outcomes of isolated primary CABG in groups of patients with mild (GFR 60-89 ml/min/1.73 m 2 ; n = 569), moderate (GFR 30-59 ml/min/1.73 m 2 ; n = 230) and severe (GFR 15-29 ml/min/1.73 m 2 ; n = 24) renal insufficiency with a group of patients with normal renal function (GFR 6 90 ml/min/1.73 m 2 ; n = 229). A total of 1,055 patients in this study were categorized into 5 groups according to the National Kidney Foundation guidelines based on GFR.…”
mentioning
confidence: 99%
“…Such factors are: the coronary anatomy before the bypass procedure, the anatomical features of the graft (e.g. arterial or venous graft and the histopathologic features), comorbid diseases (including diabetes, hyperlipidemia, hypertension, smoking and renal failure [4]) and the effectiveness of medical treatment. …”
mentioning
confidence: 99%
“…16 Nevertheless, CKD is an important marker of prognosis in different populations of patients with CAD. Studies of patients presenting with non-ST elevation MI 17 as well as patients undergoing coronary artery bypass graft surgery 18,19 or percutaneous coronary intervention 20 have demonstrated that reduced eGFR is associated with increased event rates.…”
Section: Discussionmentioning
confidence: 99%